443,517 views
14 votes
14 votes
Please help me with this homework using the substitution method

Please help me with this homework using the substitution method-example-1
User Qwerky
by
2.7k points

1 Answer

11 votes
11 votes

Answer:

(5, -2)

Explanation:

Let's solve the first equation for x: If x + y = 3, and if we subtract y from both sides, we get x = 3 - y. Next, substitute 3 - y for x in the second equation:

3(3 - y) + 2y = 11, or

9 - 3y + 2y = 11

Combining like terms: -3y + 2y = 11 - 9, or

-y = 2, or y = -2.

Then, from the equation x = 3 - y, which we found earlier,

x = 3 - (-2) = 5

Then the solution is (5, -2)

User Mcneil
by
3.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.